Implementasi Menejemen Program Takhfidzul Qur’an Dalam Peningkatan Kompetensi Lulusan Di MTs Darul Ulum Ngabar Kecamatan Jetis Kabupaten Mojokerto - Muhaimin, Muhaimin (RISDA : Jurnal Pemikiran dan Pendidikan Islam, 2021)
The tahfidzul Qur'an program, which is usually implemented in Islamic boarding schools, is actually able to be implemented at an advanced level, namely Madrasah Tsanawiyah Darul Ulum Ngabar Jetis Mojokerto. The school has implemented the Qur'an tahfidz program very neatly and structured so that I feel interested in researching it, so that students who graduate have very qualified competencies in developing memorizing the Qur'an, for that reason the researchers gave this research the title Management Implementation The Takhfidzul Qur'an Program in Increasing the Competence of Graduates at MTs Darul Ulum Ngabar, Jetis District, Mojokerto Regency by focusing on how to implement the management of the Qur'an takhfidz program in increasing the competence of graduates at MTs Darul Ulum Ngabar, Jetis District, Mojokerto Regency. The research method uses qualitative methods with data collection techniques using observation, interviews and documentation. Data collection techniques using the theory of Miles and Hubarman, data reduction, data display and Conclusions drawing/verifying. The implementation of the management of the tahfidzul qur'an program at Madrasah Tsanawiyah Darul Ulum Ngabar, including the lessons is very supportive with the time allocation that has been determined by the madrasa which is a condition for increasing the competence of madrasa graduates. In the implementation of tahfidz program management, there are planning, process and evaluation.